Budaya Pelaporan Insiden Keselamatan Pasien Terintegrasi Melalui SIMRS - Kristina Ana; Krisna Yetti; Ade Suhendri; Anik Maryunani (Journal of Telenursing (JOTING), 2023)
This research aims to identify problems in reporting patient safety incidents, conduct analysis, prepare a plan of action, implement innovations in the form of integrated patient safety incident reporting culture management through the Hospital Management Information System (SIMRS), and carry out evaluations. The research method used is a case report using the ADDIE approach to managing an integrated patient safety incident reporting culture through the Hospital Management Information System (SIMRS). The research results show that the culture of reporting patient safety incidents is not yet optimal, incident reporting has yet to be integrated through SIMRS, and there are no guidelines and Standard Operational Procedures (SPO) for reporting patient safety incidents through SIMRS. In conclusion, incident reporting is influenced by various factors, namely human factors (not all safety incidents have been reported, not yet knowing how to report patient safety incidents using SIMRS), materials (work instructions already exist (manual reporting flow SOP, reporting SPO, and writing via the Home Management Information System Hospital (SIMRS) does not yet exist) method (Integrated incident reporting flow with SIMRS does not yet exist), and machine (Reporting application via the Hospital Management Information System (SIMRS) does not yet exist). Keywords: Reporting Culture, Innovation, Patient Safety Incidents, Information Systems Hospital management